2014
DOI: 10.1371/journal.pone.0093310
|View full text |Cite
|
Sign up to set email alerts
|

Metformin and Berberine Prevent Olanzapine-Induced Weight Gain in Rats

Abstract: Olanzapine is a first line medication for the treatment of schizophrenia, but it is also one of the atypical antipsychotics carrying the highest risk of weight gain. Metformin was reported to produce significant attenuation of antipsychotic-induced weight gain in patients, while the study of preventing olanzapine-induced weight gain in an animal model is absent. Berberine, an herbal alkaloid, was shown in our previous studies to prevent fat accumulation in vitro and in vivo. Utilizing a well-replicated rat mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
50
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(51 citation statements)
references
References 63 publications
0
50
0
1
Order By: Relevance
“…1, 2, 6 and 7). Although, our data still demonstrated that berberine had some effect on body weight loss, maybe due to its lipid-lowering effects [38] and inhibition of food and water intake [39]. Importantly, we found that berberine was not toxic to podocytes under the conditions used, except for a moderate reduction in cell viability at higher concentrations (Fig.…”
Section: Discussionmentioning
confidence: 56%
“…1, 2, 6 and 7). Although, our data still demonstrated that berberine had some effect on body weight loss, maybe due to its lipid-lowering effects [38] and inhibition of food and water intake [39]. Importantly, we found that berberine was not toxic to podocytes under the conditions used, except for a moderate reduction in cell viability at higher concentrations (Fig.…”
Section: Discussionmentioning
confidence: 56%
“…Other clinical trials also showed a similar effect of metformin in attenuating SGA-induced weight gain [18,[20][21][22][23]. A recent study reported that both metformin and berberine treatment did not affect food intake, but significantly prevented olanzapine-induced brown fat loss [24]. The same author further found that uncoupled protein-1 (UCP 1 ) expression was significantly increased after co-treatment of metformin and olanzapine, compared with olanzapine only treatment [24].…”
Section: Introductionmentioning
confidence: 85%
“…A recent study reported that both metformin and berberine treatment did not affect food intake, but significantly prevented olanzapine-induced brown fat loss [24]. The same author further found that uncoupled protein-1 (UCP 1 ) expression was significantly increased after co-treatment of metformin and olanzapine, compared with olanzapine only treatment [24]. In addition, metformin and rosiglitazone can also reduce glucose intolerance and insulin resistance in patients treated with SGAs [25,26].…”
Section: Introductionmentioning
confidence: 99%
“…BBR can also prevent weight gain induced by OLZ via the UCP-1-related pathway in rats [39]. In addition, pharmaceutical compositions containing BBR could also be used to treat or prevent weight gain and obesity associated with anti-psychotic drugs [40].…”
Section: Discussionmentioning
confidence: 99%